Situations and Trends of World and Thailand Health Tourism - Kieanwatana, Komsit; al., et (Journal of Cultural Approach, 2018)
Situations and trends of Medical Tourism and Wellness tourism reveal that Asia is one of destinations for which tourists opt to visit since there are several hospitals of high caliber and world-class standard and medical fees are relatively less expensive. In the medical tourism, Thailand is ranked at the eighteenth of the world. Moreover, the growth rate of wellness tourism is approximately 9.1% per year. The regions which are most visited by wellness tourists are North America and Asia-Pacific. Furthermore, the market value of wellness tourism of Thailand inclines to continuously grow every year.